Antibacterial action of the essential oil of Origanum vulgare: a review of the literature (Research, Society and Development, 2023)
Objective: To evaluate the possible use of Origanum vulgare essential oil as an antibiotic option to combat antibiotic-resistant bacteria of clinical importance. Methodology: This is a literature review in which a search was conducted in the Google Academic, PUBMED and LILACS databases using a time cut from 2012 to 2022, with the descriptors "essential oil"; "Origanum vulgare"; "antibacterial" and "antibiotic". Results: The review included 10 studies that evaluated the relationship between Origanum vulgare essential oil and antibiotic-resistant bacteria of clinical importance.  Discussion: The essential oil of Origanum vulgare (oregano) has numerous described biological actions, of which stands out the antimicrobial activity. This activity is attributed, mainly, to its major component carvacrol, which has recognized bactericidal activity, besides the constituents γ-terpinene and p-cymene, which may present synergistic action constituents of the oil. The oil will have the cell membrane as its main attack target, and its efficacy depends on several factors, such as the harvesting site, the part of the plant used, and the way the oil is extracted. In addition, in some studies, oregano essential oil obtained greater efficacy against some pathogens compared to the antibiotic. Conclusion: The study suggests that oregano essential oil is effective in combating clinically important bacteria and may be studied as an option to combat resistant bacteria with little or no treatment option.